IMPLEMENTATION OF READING INTEREST THROUGH THE READING CORNER PROGRAM IN SD - Suci Okta Piyana; Nazurty Nazurty; Syahrial Syahrial; Afreni Hamidah (Jurnal Mantik, 2022)
This research was conducted to find out how the implementation of reading interest through the reading corner program at SD Negeri 198/III Kemantan Tinggi. This research was conducted from January to February 2021 at SD Negeri 198/III Kemantan Tinggi. This research is a phenomenological qualitative research. The subjects in the study were classroom teachers and students at SD Negeri 198/III Kemantan Tinggi, Kec. East Warm Water, Kab. Kerinci, Prov. Jambi. Collecting data in this study using observation, interviews and documentation. The results of the research at SD Negeri 198/III Kemantan Tinggi showed that with the existence of a reading corner in each class, students had a high interest in reading, this can be seen from the reading activities carried out by students during break time, when learning hours have not started.